Exploiting evolutionary steering to induce collateral drug sensitivity in cancer - Ahmet Acar (Nature Portfolio, 2020)
Evolutionary steering uses therapies to control tumour evolution by exploiting trade-offs. Here, using a barcoding approach applied to large cell populations, the authors explore evolutionary steering in lung cancer cells treated with EGFR inhibitors.